Gaucher’s Disease - A Rare Cause of Massive Splenomegaly - Rahman, Farzana; Sayeed, SK Jakaria Been; Rahman, Sabrina; Kabir, AKM Humayon; Rahman, Md Mujibur (Journal of Medicine, 2019)
Gaucher’s disease (GD) is a lysosomal storage disorder due to glucocerebrosidase deficiency; it’s one of the rare genetic diseases for which therapy is now available. Lysosomal storage of the substrate in cells of the reticuloendothelial system leads to multisystem manifestations, including involvement of the liver, spleen, bone marrow, lungs, and nervous system. Three different subtypes have been identified: Type 1, non-neuropathic form, adult onset; type 2, acute neuropathic form, infantile onset; type 3, neuropathic form, juvenile onset. The diagnosis is confirmed by presence of less than 15% activity of the enzyme Glucocerebrosidase in peripheral leucocyte with presence of Gaucher cells in macrophase monocyte system, is the pathological hallmark. Enzyme replacement therapy (ERT) is now available. We are reporting a case here which presented with cytopenia and massive splenomegaly. This case has been presented to focus on the importance of clinical examinations, differentiating from other diseases of similar manifestations, enzyme activity and bone marrow study for early diagnosis. J MEDICINE JUL 2019; 20 (2) : 98-101